Implementasi Algoritma C4.5 untuk Klasifikasi Produktivitas Bebek Petelur Peternakan Tradisional - Willy Rumapea; Ummul Khair (Universitas Harapan Medan, 2025)
The utilization of technology across various sectors has proven effective in addressing numerous related challenges, including in the field of animal husbandry. One recurring issue in the duck farming business owned by Mrs. Juntak is the determination of duck productivity. Making decisions on whether a duck is categorized as productive or not is a critical process that directly impacts the profit gained from the sale of its eggs. On the other hand, high market demand compels farmers like Mrs. Juntak to consistently provide products in sufficient quantity and with high quality. Therefore, identifying ducks with high productivity is essential to support both market demand and sales performance. This study applies data classification using the C4.5 algorithm, a well-established method for constructing decision tree models. The C4.5 algorithm is an extension of the earlier ID3 method, offering greater sensitivity in determining decisions based on the features used. The aim of this research is to identify the most influential determining factors and their derivatives that affect the productivity of laying ducks. The final output of the study is a branched decision tree that contains valuable insights into the key factors influencing duck productivity. The results indicate that feed is the most significant factor affecting the productivity of laying ducks, compared to other variables considered in the study.